2019
DOI: 10.1016/j.celrep.2019.09.023
|View full text |Cite
|
Sign up to set email alerts
|

HDAC4 Controls Muscle Homeostasis through Deacetylation of Myosin Heavy Chain, PGC-1α, and Hsc70

Abstract: Graphical AbstractHighlights d HDAC4 is an active enzyme d HDAC4 deacetylates myosin heavy chain, PGC-1a, and Hsc70 d HDAC4 inhibition increases myosin heavy chain and PGC-1a protein levels d Maintaining acetylation of myosin heavy chain and Hsc70 prevents atrophy SUMMARY HDAC4, a class IIa histone deacetylase, is upregulated in skeletal muscle in response to denervationinduced atrophy. When HDAC4 is deleted postnatally, mice are partially protected from denervation. Despite the name ''histone'' deacetylase, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 57 publications
(48 reference statements)
6
68
0
Order By: Relevance
“…The leaving HDAC5 releases its repressive effect on Baf60c and enhancing insulin-independent AKT activation (Meng et al, 2017). Using specific inhibitor of class IIa HDAC activity, myosin heavy chain, PGC-1α, and heat-shock cognate (HSC70) are confirmed to be one of the substrates of HDAC4 in denervation-induced atrophy muscle in comparison with acetylated protein enrichment with untreated group (Luo et al, 2019). Taken together, Class IIa HDACs play critical roles in exercise capacity, remodeling, and nutrient sensing of skeletal muscles (Figure 3).…”
Section: Regulation Of Class II Hdacs On Fiber-type Switch Mitochondmentioning
confidence: 98%
“…The leaving HDAC5 releases its repressive effect on Baf60c and enhancing insulin-independent AKT activation (Meng et al, 2017). Using specific inhibitor of class IIa HDAC activity, myosin heavy chain, PGC-1α, and heat-shock cognate (HSC70) are confirmed to be one of the substrates of HDAC4 in denervation-induced atrophy muscle in comparison with acetylated protein enrichment with untreated group (Luo et al, 2019). Taken together, Class IIa HDACs play critical roles in exercise capacity, remodeling, and nutrient sensing of skeletal muscles (Figure 3).…”
Section: Regulation Of Class II Hdacs On Fiber-type Switch Mitochondmentioning
confidence: 98%
“…HDAC4 also mediates induction of growth arrest and DNA damage-inducible 45α (Gadd45a), a small myonuclear protein that is required for denervation-induced muscle atrophy. A recent study, which aimed at uncovering additional HDAC4 substrates in skeletal muscle, identified myosin heavy chain, PGC-1α, and heat shock cognate 71 kDa protein (Hsc70) to all be regulated by HDAC4 [ 163 ]. Thus, HDAC4 is an important regulator of muscle trophism in denervation and NMJ disorders, but more research is required to better understand its signaling network and mechanism of action within skeletal muscle.…”
Section: Transcriptional Regulators Of Muscle Massmentioning
confidence: 99%
“…This suggests that TIP60 acts as a mediator, linking HIF-1α to HIF-1α target genes. In human cells, the 18 deacetylases are divided into four classes [ 131 ]. The class II is divided into two subclasses, IIa (HDAC4, HDAC5, HDAC7 and HDAC9) and IIb (HDAC6 and HDAC10), among which HDAC4, HDAC5 and HDAC6 are thought to be related to the regulation of HIF functional activity [ 2 , 131 , 132 ].…”
Section: Epigenetic Regulation Of Hifs Activitymentioning
confidence: 99%
“…In human cells, the 18 deacetylases are divided into four classes [ 131 ]. The class II is divided into two subclasses, IIa (HDAC4, HDAC5, HDAC7 and HDAC9) and IIb (HDAC6 and HDAC10), among which HDAC4, HDAC5 and HDAC6 are thought to be related to the regulation of HIF functional activity [ 2 , 131 , 132 ]. Within VHL-positive cancer cell lines, HDAC4 inhibition by shRNA increases HIF-1α protein acetylation levels, while HDAC4 overexpression decreases HIF-1α acetylation levels [ 133 ].…”
Section: Epigenetic Regulation Of Hifs Activitymentioning
confidence: 99%